Mesjid-mesjid tua di Jakarta - Heuken, Adolf (Jakarta : Yayasan Cipta Loka Caraka, 2003)
History of mosques in Jakarta from the 17th to the 19th centuries.
Includes bibliographical references (pages: 108-110).
Keywords: Mosques -- Indonesia -- Jakarta